2013
DOI: 10.1080/13803395.2013.844771
|View full text |Cite
|
Sign up to set email alerts
|

Education level predicts retrospective metamemory accuracy in healthy aging and Alzheimer’s disease

Abstract: The current study investigated the effect of education on retrospective metamemory accuracy in 143 healthy older adults and 143 early to moderate AD patients, using retrospective measures of confidence in the accuracy of retrieval responses in an episodic odor recognition memory task. Relative confidence accuracy was computed as the difference between confidence judgments for correct and incorrect responses. In both AD patients and controls, individuals reporting 17 years of education or more had significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 59 publications
4
19
0
2
Order By: Relevance
“…That is, not having the ability to engage cognitive networks to compensate for memory problems means that those difficulties are not detected. This is consistent with a recent study demonstrating a relationship between higher education levels (another proxy for cognitive reserve) and greater metamemory accuracy in Alzheimer’s Disease (Szajer & Murphy, 2013). Additionally of note, both cognitive reserve and metacognitive accuracy have been positively associated with external compensatory strategy use (Garrett, Grady, Hasher, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…That is, not having the ability to engage cognitive networks to compensate for memory problems means that those difficulties are not detected. This is consistent with a recent study demonstrating a relationship between higher education levels (another proxy for cognitive reserve) and greater metamemory accuracy in Alzheimer’s Disease (Szajer & Murphy, 2013). Additionally of note, both cognitive reserve and metacognitive accuracy have been positively associated with external compensatory strategy use (Garrett, Grady, Hasher, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…However, it has been suggested that educational level can influence metamemory, with evidence that older adults with higher educational level have a more accurate level of confidence in retrospective metamemory. 6 It is worth noting that in our study the MMQ was suitable for elders with different educational background (4 to 22 years of schooling). However, we recommend that examiners supervise individuals with low educational level more closely in order to check for instruction comprehension and possible mistakes.…”
Section: Discussionmentioning
confidence: 78%
“… 5 These aspects are considered important in directing the use of memory processes in overall decision making. 6 Also, authors have argued that the metamemory definition should also include feelings and emotions about memory, along with self-efficacy associated with memory, 5 , 7 which is related to confidence level regarding one's own memory ability. 8 Metamemory has been studied within the field of psychology of aging to understand changes in memory abilities during aging.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the self-rated confidence was a valid reflection on their performance, as in the younger group. It has been demonstrated that meta-memory is preserved in elderly individuals, despite lower levels of explicit memory performance on the same learnt material ( Halamish, McGillivray, & Castel, 2011 ), though this outcome has been suggested to depend on high education levels (see Szajer & Murphy, 2013 ).…”
Section: Discussionmentioning
confidence: 99%